Trends, and tumor characteristics of lung cancer and malignant pleural mesothelioma in the East of Libya - Eldukali, Wail; Omran, Khaled; Azzuz, Raouf (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Background: Lung cancer is the most common cancer worldwide and the leading cancer killer. Lung cancer is classified histologically into two types; small-cell lung cancer and nonsmall-cell lung cancer (NSCLC) (squamous cell carcinoma, adenocarcinoma (AC), large cell carcinoma [LCC]). Malignant pleural mesothelioma is a rare thoracic tumor. We aimed to provide comprehensive epidemiological data about lung cancer in the eastern part of Libya. Patients and Methods: A retrospective medical records review of lung cancer patients attending the oncology department of Benghazi Medical Center from January 1, 2006 to December 31, 2015. Results: There were 684 lung cancer cases out of 7725 total registered cancer cases (8.85%), 627 were male (91.7%, median age 63.5), and 57 females (8.3%, median age 64). NSCLC was the dominant histology 78.5%, SCLC 11%, and malignant mesothelioma 2.5%. NSCLC subtypes were AC (35.1%), squamous carcinoma (25.7%), LCC (4.6%), and not otherwise specified (12.6%). Only 30.6% of cases were diagnosed in Libya, the most commonly used diagnostic modalities were bronchoscopic biopsy 46.6%, and computed tomography guided biopsy 17.4%. Only 18 cases were tested for epidermal growth factor receptor sensitizing mutations and anaplastic lymphoma kinase rearrangement fusion. Stage IV was the most common initial stage for NSCLC 60%, malignant mesothelioma 47.1%, and 74.7% of SCLC presented with extensive disease. Only 42.9% of males and 5.3% of female lung cancer patients were smokers. Conclusions: Lung cancer is a major health burden in Libya, and it is increasing in incidence; this epidemiological study tries to put this problem into public health and clinical perspective.
Keywords: Adenocarcinoma; asbestos; large cell carcinoma; lung cancer; malignant pleural mesothelioma; nonsmall-cell lung cancer; small-cell lung cancer; smoking; squamous cell carcinoma